Предмет: Алгебра, автор: atkevicv91

Пожалуйста помогите ​

Приложения:

Ответы

Автор ответа: petrpetrbayandin
0

Ответ:

\frac{135}{a^{2}-6a }*\frac{a-6}{3a+9} -\frac{5a}{a+3}=\frac{135*(a-6)}{a(a-6)3(a+3)}-\frac{5a}{a+3}=\frac{45}{a(a+3)}-\frac{5a}{a+3}=\frac{45a-5a^{2} }{a(a+3)}=\frac{5(9-a^{2}) }{a(a+3)}=\frac{5(3-a)(3+a)}{a(a+3)}=\frac{5(3-a)}{a}=\frac{15-5a}{a}

Объяснение:

Автор ответа: gnomiha211
0
Решение на фотографии
Приложения:
Похожие вопросы
Предмет: Математика, автор: petruschinakaty1